Application of Problem-Based Learning Model to Students' Mathematic Communication Ability - Putri Madhavia; Atma Murni; Sehatta Saragih (Magister Mathematic Education Department Faculty of Teacher Training and Education Universitas Riau, 2021)
This article describes applying the Problem-Based Learning (PBL) model on Mathematical Communication Ability. The research in this journal is an experimental study using pretest-posttest control group design with a population of seventh-grade students of SMP Negeri in Kuantan Singingi Regency, divided into three school levels: high, medium, and low schools. From each school, two classes were randomly selected as the experimental class and the control class. The research instrument was the Mathematical Communication Ability test questions. The data collection technique is done by testing. Data were analyzed using t-test and one-way ANOVA. The results showed an effect of PBL application on mathematical communication skills in terms of all students. The effect of PBL application on mathematical communication skills in terms of school-level shows that for the high school level, students are better than students using conventional learning, while at the medium and low school level, there is no significant effect.